See you in the cosmos - Cheng, Jack, 1983- (Dial Books for Young Readers, 2017)
"Eleven-year-old Alex Petroski, along with his dog, Carl Sagan, makes big discoveries about his family on a road trip and he records it all on a golden iPod he intends to launch into space"--